THE ROLE AND SIGNIFICANCE OF COSTEN’S SYNDROME IN DYSFUNCTIONAL CONDITIONS OF THE TEMPOROMANDIBULAR JOINTS - V.F. Makeev; U.D. Telishevska; O.D. Telishevska; M.Yu. Mykhailevych (Український стоматологічний альманах)
Temporomandibular joint disease (TMJ) is one of the most pressing problems of modern dentistry, on the one hand, the frequency of pathology of the temporomandibular joint, and on the other hand - the complexity of diagnosis.